3(a+8)+1=-3(3-7a)-2

Simple and best practice solution for 3(a+8)+1=-3(3-7a)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(a+8)+1=-3(3-7a)-2 equation:



3(a+8)+1=-3(3-7a)-2
We move all terms to the left:
3(a+8)+1-(-3(3-7a)-2)=0
We add all the numbers together, and all the variables
3(a+8)-(-3(-7a+3)-2)+1=0
We multiply parentheses
3a-(-3(-7a+3)-2)+24+1=0
We calculate terms in parentheses: -(-3(-7a+3)-2), so:
-3(-7a+3)-2
We multiply parentheses
21a-9-2
We add all the numbers together, and all the variables
21a-11
Back to the equation:
-(21a-11)
We add all the numbers together, and all the variables
3a-(21a-11)+25=0
We get rid of parentheses
3a-21a+11+25=0
We add all the numbers together, and all the variables
-18a+36=0
We move all terms containing a to the left, all other terms to the right
-18a=-36
a=-36/-18
a=+2

See similar equations:

| 57-3=2y+9 | | 8a+4=6a+4 | | 3(2-k)=-3k=2 | | x/4-19=20 | | -3(6+3x)=-(6x+3) | | 6+8x=11x | | y/5+10=11 | | -3x+10=-38 | | 6(m-4)+5=-5(6-m) | | -2x+8(x+7)=7+5(1-x) | | -8-(6-8m)=2(m-1) | | 51=5(3a+6)-8 | | 7(4-4x)=-8(1+3x) | | 30.25x=60 | | 17=3-2(2f-1) | | 5x+3–3x+2=35 | | -(7x-1)+14=21 | | 8+w/2=11 | | 0.05x=37.25 | | 2m=78 | | 13-3k=7 | | 26+4.25.x=60 | | -3(-6b-4)=6(4b+6) | | -6u-36=−42 | | -4(m-1)=-8 | | -6u-36= | | 16/4=v | | 9.43=k−9.64 | | 2(4x+2)+x=9x-4 | | 30+x=3/5 | | 19t-16t=48 | | 3/4(8x−12)=4x−4 |

Equations solver categories